Circular Road, Queen's Park South, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
A view of some of the homes which were located on the southern side of the Queen's Park Savannah circa 1910.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Savannas--Trinidad and Tobago; Architecture, Domestic--Trinidad and Tobago; Dwellings--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Queen's Park Savannah